2011
DOI: 10.1111/j.1365-2486.2011.02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Using a climatic niche model to predict the direct and indirect impacts of climate change on the distribution of Douglas‐fir in New Zealand

Abstract: Climate change is likely to have major impacts on the distribution of planted and natural forests. Herein, we demonstrate how a process-based niche model (CLIMEX) can be extended to globally project the potential habitat suitable for Douglas-fir. Within this distribution, we use CLIMEX to predict abundance of the pathogen Phaeocryptopus gaeumannii and severity of its associated foliage disease, Swiss needle cast. The distribution and severity of the disease, which can strongly reduce growth rate of Douglas-fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In fact, distance inland and elevation were collinear with several environmental variables examined in this study. Our observations are also in agreement with studies that suggested that high summer temperatures inhibit the growth of N. gaeumannii (Rosso & Hansen, 2003), resulting in lower SNC severity (Lee et al, 2017;Manter et al, 2005;Stone, Coop, et al, 2008;Stone et al, 2007;Watt, Stone, Hood, & Manning, 2011;Watt et al, 2010;Zhao et al, 2012). Our observations are also in agreement with studies that suggested that high summer temperatures inhibit the growth of N. gaeumannii (Rosso & Hansen, 2003), resulting in lower SNC severity (Lee et al, 2017;Manter et al, 2005;Stone, Coop, et al, 2008;Stone et al, 2007;Watt, Stone, Hood, & Manning, 2011;Watt et al, 2010;Zhao et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, distance inland and elevation were collinear with several environmental variables examined in this study. Our observations are also in agreement with studies that suggested that high summer temperatures inhibit the growth of N. gaeumannii (Rosso & Hansen, 2003), resulting in lower SNC severity (Lee et al, 2017;Manter et al, 2005;Stone, Coop, et al, 2008;Stone et al, 2007;Watt, Stone, Hood, & Manning, 2011;Watt et al, 2010;Zhao et al, 2012). Our observations are also in agreement with studies that suggested that high summer temperatures inhibit the growth of N. gaeumannii (Rosso & Hansen, 2003), resulting in lower SNC severity (Lee et al, 2017;Manter et al, 2005;Stone, Coop, et al, 2008;Stone et al, 2007;Watt, Stone, Hood, & Manning, 2011;Watt et al, 2010;Zhao et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…We therefore used distance inland as a proxy for continentality, a complex combination of multicollinear environmental factors that vary along this geographic gradient (Zhao et al, 2011) (Lee et al, 2013(Lee et al, , 2017(Lee et al, , 2016Manter et al, 2005;Stone, Coop, et al, 2008;Stone et al, 2007;Watt et al, 2010). Climate change (i.e., increasingly warmer winter temperatures) will likely exacerbate SNC severity in the western Coast Range leading to an intensification of symptoms in areas already affected by SNC, as well as an expansion of the area affected by SNC (Coop & Stone, 2010;Lee et al, 2017;Stone, Coop, et al, 2008;Watt et al, 2011Watt et al, , 2010. Climate change (i.e., increasingly warmer winter temperatures) will likely exacerbate SNC severity in the western Coast Range leading to an intensification of symptoms in areas already affected by SNC, as well as an expansion of the area affected by SNC (Coop & Stone, 2010;Lee et al, 2017;Stone, Coop, et al, 2008;Watt et al, 2011Watt et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Within the SNC impact zone along the coast of Oregon and Washington, disease severity is associated with a combination of mild winter temperatures and high leaf wetness in spring (Manter et al., ; Stone, Coop, et al., ) as well as mild summer temperatures ranging between the optimum temperatures for ascospore germination and germ tube growth at 18°C and 22°C, respectively (Capitano, ). These climatic conditions for disease severity have also been verified in New Zealand (Watt et al., ). The maturation period for P. gaeumannii ranges from 1 to 2 years in some areas of the Coast Range to 4–7 years in the Cascade Range of Oregon and Washington as evidenced by pseudothecia on young and older needles, respectively (Stone, Capitano, et al., ).…”
Section: Introductionmentioning
confidence: 61%
“…In this case, climate (i.e., temperature and precipitation gradients) may be an important factor influencing the different distribution patterns of the two lineages across the landscape. There is strong evidence that climatic variables such as winter temperature and precipitation in the spring and early summer influence the abundance of P. gaeumannii, and thus disease [22][23][24][25][26]. The western Oregon Coast Range is particularly suited to support abundant populations of P. gaeumannii because it receives greater spring precipitation, and has generally milder winter, and cooler summer, temperatures than the rest of the region.…”
Section: Phylogeographymentioning
confidence: 99%